The separation of intracellular serum albumin from rat liver - Judah, J. D. (1971)
1. Antibody precipitation of serum albumin from rat liver extracts yields impure preparations of the protein. 2. When rat liver is labelled with l-[1-(14)C]leucine, antibody precipitation of albumin leads to material that is contaminated with a protein or proteins of very high specific radioactivity. Only 10–25% of the radioactivity of the antibody precipitate is associated with serum albumin. 3. A chromatographic procedure is described that can be used to separate radiochemically pure serum albumin from antibody precipitates obtained from extracts of rat liver. 4. Extracellular albumin secreted by liver slices yields a precipitate with antibody which contains much less radioactive impurity. About 70–90% of the radioactivity is associated with serum albumin. Serum albumin separated by antibody precipitation from rat serum labelled in vivo was not contaminated with the radiochemical impurities associated with intracellular albumin. 5. A simple method is described of obtaining the content of serum albumin in rat liver extracts by the technique of isotope dilution and ion-exchange chromatography.